(untitled) (Research, Society and Development, 2020)
Aluminosilicates are commonly used as technological additives in industrial poultry due to their action as feed binders and as mycotoxin adsorbents, however when supplied in greater quantities, they can act in several other physiological functions of the poultry, increasing in performance. Therefore, the objective of this bibliographic review is to elucidate the action of different aluminosilicates, and the possibility of using them in the nutrition of birds of zootechnical interest. With the increase in the use of pelleted feed in industries, aluminosilicates can be used, increasing the durability and quality of pellets, through the absorption of moisture. Due to the presence of electrical charges, these additives have a binding capacity of about 86% to 97% of the amount of mycotoxins present in the feed, adsorbing them. This same property allows them to bind to toxins and bacteria in the intestine, and their ability to absorb water significantly impacts the reduction of moisture in excreta. All of these characteristics can result in better performance, well-being and quality of poultry products. However, due to this presence of fillers, aluminosilicates can adsorb vitamins, minerals and other additives present in diets. Therefore, the use of aluminosilicates is a viable alternative in diets for broilers, chickens, quails and turkeys, however, further studies must be carried out in order to determine which of these minerals can be used and in what concentrations.